Firm Size In Moderate Factors Affecting Islamic Social Reporting - Norma Setiyani; Adelina Citradewi (LPPM ISNJ Bengkalis, 2023)
This research aims to show the influence of profitability, leverage, and size of the board of commissioners on Islamic social reporting (ISR) disclosure with company size as a moderating variable in Jakarta Islamic Index (JII) companies for 2019-2021. The population of this research was 30 companies, and the selected sample was 13 companies using purposive sampling, so the total sample data is 39. The source used secondary data from company annual reports obtained through each website. Data analysis uses moderated regression analysis (MRA). This research confirms that profitability has a positive and significant effect on ISR disclosure. The leverage and size of the board of commissioners do not affect ISR disclosure. Company size can moderate the effect of profitability on ISR disclosure. Company size cannot moderate the influence of leverage and board size on ISR disclosure. This research shows that effective asset management can increase ISR disclosure for businesses that achieve high profitability, so the research results can be a reference for business management when making ISR policies, especially those related to Islamic business. This research can also be used as evaluation material for company management in determining policies related to ISR, especially in Islamic-motivated companies.